Performance Analysis of the LoRaWAN Protocol for Data Transmission In Urban Area Scenarios - Muhammad, Fathan; Syaiful , Syaiful (Green Publisher Indonesia, 2023)
Long Reach Wide Region Organization (LoRaWAN) is a kind of organization for remote media transmission region intended to empower far off correspondence with significant distance correspondence and low piece rate. LoRaWAN can be utilized on correspondence networks that have a wide reach utilizing end gadgets. LoRaWAN offers a great many benefits to the test of IoT execution, however the ongoing execution of LoRaWAN innovation is still exceptionally restricted, requiring practicality testing and examination how much LoRaWAN innovation is equipped for being carried out in metropolitan regions in Indonesia. In this examination, an investigation of the exhibition of the LoRaWAN convention for information transmission with metropolitan region situations in Malang City is done. The strategy utilized in this study is to reproduces LoRaWAN convention in Organization Test system 3 (NS-3) application by changing the boundaries to decide the impact on the quantity of end gadgets, sweep of the passage reach, and information sending period to the boundaries throughput and parcel misfortune. From the aftereffects of exploration demonstrated that for the utilization of convention LoRaWAN in metropolitan regions, the more end gadgets utilized, the more prominent the throughput esteem and the more prominent the worth of bundle misfortune acquired. What's more, the more extensive the region required, the throughput and bundle misfortune acquired are steady. And afterward, the bigger the time of information transmission, the more modest the throughput esteem is acquired and the more modest the worth of bundle misfortune got